GOD’S INTERVENTION REVISITED: AN ILLUMINATION OF HIS CONTINUOUS PRESENCE - A.C. Pieterse (Acta Theologica)
The belief that the triune God intervenes in creation is one of the foundations of the faithful’s interaction with their creator. However, these beliefs lead to a discrepancy with natural science regarding God’s relationship with natural laws. Were God to intervene in nature, he would apparently be breaking, suspending or simply not following the lawful order he created in the universe. From a theological perspective, the word “intervention” is also not helpful. If God “ventures” into creation, where does he come from, and for how long would he stay? I propose that God does “intervene” in creation, but not from somewhere above space and time, breaking into his own created order, and uprooting natural laws. What we might call “intervention” is rather a specific illumination of his ongoing revelatory work in creation. The value of this hypothesis may lie in connecting God’s upholding work and his special work.